IN SEARCH OF THE KEYS OF NEW HUMANISM: BAKHTIN, THE KEYMAKER OF THE 21.ST CENTURY - Souza, Fábio Marques; Miotello, Valdemir; Camargo Junior, Ivo di (Saberes: Revista interdisciplinar de Filosofia e Educação, 2023)
In Matrix reloaded a very emblematic figure appears to give meaning to the plot: the Keymaker. In this essay we bring Mikhail Bakhtin as this Keymaker, a man whose philosophy leads us to new ways of thinking and to the constitution of a new human being, full of alterity and surplus of seeing the others.